LEARNERS’ ABILITY TO NEGOTIATE MEANING IN INTERACTIONAL CONVERSATION - Nurazizah, Nuki; Agustien, Helena I. R.; Sutopo, Djoko (ELT Forum: Journal of English Language Teaching, 2018)
Negotiation is one kind of ways in order to interact with other people. Doing negotiation means that participants are able to reveal what they feel and think. For this study, observation was done before recording. Audio recording is the primary data besides there was also note. The note is about the class’ situations that were not included in the recording. Then, the data is transformed into transcription. After the transcript is made, the data is able to be analyzed. Results indicate that the learners mostly negotiate well. They produce statements in compliance with mood elements. They also have various kinds of mood types in the conversation. The ways that the students negotiate meaning in order to get the meaning across are countering the interlocutors’ responds, responding the teacher by giving statement that exactly suit to the teacher’s questions, and having equal turns reciprocally to convey their ideas in a conversation. In order to compensate their language problems, the students use some strategies such using minor clause, speaking in their native language, and doing non-verbal communication. In addition, there are also some grammatical problems hinder the negotiation of meaning. They ellipse a certain element of the clause. Another grammatical problem is that the students do not use fit correspondence between Finite and other elements.